Artificial Salmonella Vaccines: Salmonella typhimurium O-Antigen-Specific Oligosaccharide-Protein Conjugates Elicit Protective Antibodies in Rabbits and Mice - Svenson, Stefan B. (1981)
Several saccharides representative of the O-antigenic polysaccharide chain of Salmonella typhimurium (O antigens 4 and 12) were used as haptenic groups covalently linked to bovine serum albumin. The disaccharide abequose 1 → 3 D-mannose was synthesized, and the [Formula: see text] tetra-, octa- and dodecasaccharides were isolated after cleavage of isolated S. typhimurium O-polysaccharide chains by using bacteriophage endo-glycosidases. Rabbits immunized with the saccharide-protein conjugates suspended in Freund complete adjuvant readily responded with O4 antibody titers as high, or almost as high, as those elicited by heat-killed bacteria. The octa- and dodecasaccharide conjugates also gave rise to O12 antibody titers. The antibody response in mice differed in two ways from that seen in rabbits: mice did not respond with measurable antibody production against the disaccharide haptens, and the highest S. typhimurium lipopolysaccharide antibody response elicited by the saccharide haptens was still approximately 50-fold lower than that elicited by heat-killed bacteria. The latter difference may be a consequence of the fact that the mouse preferentially produces antibodies against the galactose residue which is terminal in the hapten but not in the native O-antigenic polysaccharide chain. Antibodies elicited in rabbits against all saccharide-protein conjugates protected passively transferred mice against intraperitoneal challenge with 100 times the 50% lethal dose of S. typhimurium SH 2201 (O4, 12) but not against challenge with S. enteritidis SH 2204 (O9, 12). The antibodies elicited by the saccharide-protein conjugates protected as well as antibodies elicited by heat-killed bacteria.